Versatility of Deep Eutectic Solvents (DESs): Green Restoration and Eco-sustainable Organic Synthesis - Strangis, Romina; Mancuso, Raffaella; La Russa Mauro Francesco; Beneduci, Roberto; Figoli, Alberto; Critelli, Salvatore (Università della Calabria, 2024)
Deep Eutectic Solvents (DESs) represent a class of unconventional solvents obtained from the mixture of two or more pure compounds, resulting in a liquid form at room temperature due to their lower melting point than those predicted for an ideal liquid mixture. They stand out from conventional solvents due to their environmental sustainability, biodegradability, and versatility, attracting attention in various fields. However, their potential application in cultural heritage restoration remains largely unexplored, given the limited number of scientific papers addressing the use of DESs in this field. This research project aims to prepare DESs and evaluate their efficacy as eco-friendly strategies for restoration practices. A first case study demonstrates the promising utility of DESs as green biocidal solvents for use in the removal of biofilms from artworks in the cultural heritage sector. A second case study highlights the ability of hydrophobic DESs, as cleaning agents, to remove aged non-polar coatings, addressing degradation products commonly encountered in restoration work on metal and stone assets. The search for new solvents, such as DESs, to replace harmful and unsafe conventional solvents used in the cultural heritage sector has shown promising results. Furthermore, due to their unique characteristics, DESs can be used as unconventional solvents in organic synthesis representing excellent substitutes for volatile organic solvents. The main advantages of their use as reaction solvents are increased reaction speed, increased reaction yield and selectivity, and the possibility of recycling the solvent/catalyst system. DESs prove to be efficient solvents in the synthesis of high-value-added organic compounds, facilitating processes such as the iodocyclization reaction and the Sonogashira and Suzuki coupling reactions. This approach underscores the versatility and potential of DESs in cultural heritage conservation and cleaning, and in synthetic chemistry, offering a viable alternative with wide applicability.
Università della Calabria. Corso di laurea in Ingegneria Ambientale. Dottorato di ricerca in: Scienze e Ingegneria dell’Ambiente, delle Costruzioni e dell’Energia (SIACE). Ciclo XXXVI
Keywords: DESs. Solventi non convenzionali. Restauro. Patrimonio culturale